Is self-reported symptom duration in individuals with patellofemoral pain an accurate measure? An observational longitudinal study - Briani, Ronaldo Valdir [UNESP]; Balotari, Ana Flávia Botta [UNESP]; Waiteman, Marina Cabral [UNESP]; Magalhães, Fernando Henrique; Bazett-Jones, David M.; de Azevedo, Fábio Mícolis [UNESP] (Elsevier, 2025)
Background: Although self-reported symptom duration of individuals with patellofemoral pain (PFP) is usually assessed for clinical and research purposes, its accuracy has never been investigated. Objectives: We followed up individuals with PFP over 15 months to determine the agreement between self-reported symptom duration and calculated symptom duration. Methods: Self-reported symptom duration of 39 participants was assessed at baseline and re-assessed at follow-up. Calculated follow-up symptom duration was determined by the summation of baseline self-reported symptom duration with the known follow-up duration. The symptom duration difference was determined by the subtraction of the calculated follow-up symptom duration and the self-reported follow-up symptom. Results: We identified a symptom duration difference of 20.1 months (95 % confidence interval: 11.2, 29.1 months), with greater differences in individuals with longer symptom duration (r² = 0.12). Conclusion: Our findings suggest that the accuracy of self-reported symptom duration measures in individuals with PFP is questionable and techniques should be used to improve it.
Keywords: Chronicity; Duration of complaints; Knee pain